Selectivity and efficacy of some herbicides in forest plant nurseries. - Del-Busto, Angelina; Bimbo, B.; Garcia-Espana, V.; Gómez-De-Barreda, Diego (2017)
A experiment was conducted in a 4 especies of forest plants nurseries Quercus ilex L. Pinus halepensis Mill, Pinus pinea L. and Pistacia terebinthus L. with the following residual herbicides simazine, isoxaben, and thiazopyr. The treatment was done in preemergence of the weeds and the crops. Simazine, isoxaben and the mixture of both herbicides were selective in the four forest plants but thiazopir was phytotoxic.